Evaluation of the trace metal supplements for a synthetic low lactose diet. Issue 6 (June 1983) - Aggett, P J; More, J; Thorn, J M; Delves, H T; Cornfield, M; Clayton, B E
Abstract : A trace element supplement used with a synthetic low lactose milk (Galactomins 17 and 18) has been evaluated by means of metabolic balance studies in 4 infants with dissacharide intolerances. The supplement was considered satisfactory for iron and manganese but increases in its zinc and copper content are probably necessary to ensure adequate retentions of these metals.